2019
DOI: 10.1088/1361-6501/aaf8ec
|View full text |Cite
|
Sign up to set email alerts
|

Void fraction measurement using an imaging and phase isolation method in horizontal annular flow

Abstract: A new imaging method was proposed to measure the void fraction of annular flow based on phase isolation technology in a horizontal circular tube. As the gas–liquid mixture passes through the phase isolation device, which is arranged upstream, a strong swirl flow is created due to centrifugal effect. The liquid phase is pushed to the tube wall and forms a uniform liquid film, while the gas phase is concentrated to the tube center and forms a gas core. This rectified core-annular flow has a more smooth and clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The uniform shape of swirl core-annular flow enables the flowrate measurement of liquid phase in gas-liquid two-phase flow by electromagnetic flowmeter to be more accurate. The authors also successfully measured the void fraction and liquid film thickness in a previous study [48] using phase isolation and an imaging method, in which we also found that phase isolation not only provides a uniform phase interface but also generates many microbubbles in the liquid film as well. Therefore, it is rational to suppose that these phase-isolation-induced microbubbles may be able to act as tracers to measure the flow of liquid film.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…The uniform shape of swirl core-annular flow enables the flowrate measurement of liquid phase in gas-liquid two-phase flow by electromagnetic flowmeter to be more accurate. The authors also successfully measured the void fraction and liquid film thickness in a previous study [48] using phase isolation and an imaging method, in which we also found that phase isolation not only provides a uniform phase interface but also generates many microbubbles in the liquid film as well. Therefore, it is rational to suppose that these phase-isolation-induced microbubbles may be able to act as tracers to measure the flow of liquid film.…”
Section: Introductionmentioning
confidence: 55%
“…Under the action of centrifugal force, the original flow pattern is redistributed into a swirl core-annular flow. With this flow pattern, the majority of the gas phase gathers into the pipe's center and forms a gas core while the liquid phase diffuses to the pipe's inner surface and forms a liquid film [48]. The interface of the two phases becomes smoother and more uniform.…”
Section: The Phase-isolation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies had been conducted on liquid film thickness employing experimental methods. The main measurement techniques can be mainly classified into acoustic [13][14][15][16], radiometric [17], electrical [18][19][20][21], and optical [22,[23][24][25][26] methods, of which electrical method [18][19][20][21] and optical method [22,[23][24][25][26] are the most widely used.…”
Section: Introductionmentioning
confidence: 99%